2022
DOI: 10.1140/epjc/s10052-022-10120-7
|View full text |Cite
|
Sign up to set email alerts
|

New Gedanken experiment on RN-AdS black holes surrounded by quintessence

Abstract: In this paper, we use the new version of Gedanken experiment to investigate the weak cosmic censorship conjecture(WCCC) for RN-AdS black holes surrounded by quintessence. The process of matter fields falling into the black hole can be regarded as a dynamic process. Since the perturbation of matter fields doesn’t affect the spacetime geometry, we propose the stability condition and assume the process of matter fields falling into the black hole satisfies the null energy condition. Based on the stability conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [34]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [34]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 94%
“…In section 3, the gravitational and electromagnetic perturbations in the Bardeen-Kiselev BH with the cosmological constant are reported. The QNMs of the Bardeen-Kiselev BH with the cosmological constant for gravitational and electromagnetic perturbations are analyzed, and we compare the frequencies with the Reissner-Nordström-de Sitter BH surrounded by quintessence (RN-dSQ) [48] in section 4. In section 5, we focus on a discussion on the greybody factor, the reflection coefficient and the total absorption cross section.…”
Section: Introductionmentioning
confidence: 99%